New and interesting fungi from Guangzhou City, South China - Yang, Kun L.; Lin, Jia Y.; Li, Guang-Mei; Yang, Zhu L. (Phytotaxa, 2025)
Towards a better understanding of fungal diversity in Guangzhou City, South China, seventeen relevant species from two phyla, two classes, six orders and fourteen families, are described and/or discussed in this study. Among them, Atramentodiscus nanshaensis represents a new apothecial family of Dothideomycetes, differing from taxa in the sister family Catinellaceae by the presence of croziers, smoother apothecial margin, and more uniformly pigmented ectal excipulum; Agaricus cantonotraminus is a new species recognized in the well-known Ag. campestris complex, phylogenetically closest to Ag. braendlei and Ag. pampeanus, but the shape and size of basidiospores are different; Hymenagaricus conghuaensis is a new species sister to Hy. splendidissimus, exhibiting similar morphology with Hy. splendidissimus, but presenting fewer and sparser squamules, and greyish brown lamellae with brownish basidiospores; Leucocoprinus phantasmaticus is a new species in the L. birnbaumii clade, differing from other Asian Leucocoprinus species by its typically lignicolous habit, whitish fragile basidiomata, and pileus squamules composed of inflated cells; Amanita huangpuensis is a new and possibly poisonous species of the Am. pseudoporphyria complex, differing from other species in this complex by a combination of small to medium-sized basidiomata, non-greyish stipe with a superior annulus and whitish to greyish volval remnants around stipe base, usually retained volval remnants on pileus, and subglobose, broadly ellipsoid to ellipsoid basidiospores sized 6–7.5 × 5–6 µm; Clitopilus zoysiae is a new species of Clitopilus sect. Scyphoides, sister to C. giovanellae, differing from other species in this section by the habit of growing on living or dead stems of Zoysia plants; Calvatia scandens is a new species recognized in Calvatia sect. Calvatia, uniquely processing tiny basidiomata, a habit of clinging on stones, sticks or bricks by rhizomorphs, ellipsoid basidiospores, and capillitia strongly encrusted with granules when mature; Termitomyces intermedius, current name for a well-known edible fungus, is threatened by an earlier name Sinotermitomyces taiwanensis, but the holotype components of the latter name are inferred as problematic and cannot be confirmed at present; Marasmiellomycena entolomatoides is a new species with remarkable tomentose basidiomata, currently placed in the heterogenous genus Marasmiellomycena but may be further revised; Floriboletus is a new genus of Boletoideae in Boletaceae, with coniodermal pileipellis differing from other genera known in this subfamily, currently comprising two species, Floriboletus tianheensis and F. puellaris; Hygrophoropsis pleurotoides is a new species with unresolved phylogenetic position, morphologically distinct by pleurotoid basidiomata with lamellate hymenophore and tiny basidiospores, assigned to the genus Hygrophoropsis for the moment; Satyrus, a genus historically proposed in Phallus s. l., is recognized as separated from Phallus s. str. with two species characterized by reddish basidiomata with a rugose pileus surface, Satyrus rubicundus and S. rugulosus, as suggested by the current phylogeny; Daedalea atypa is revised as the correct name of the so-called D. modesta previously known in South China, and Fomitopsis rubida is recognized as a later synonym of D. atypa with molecular evidence; Polyporus mesotalpae, previously known as a later synonym of Kusaghiporia talpae, is recognized as an independent species with molecular evidence from our collections, recombined as Kusaghiporia mesotalpae, representing a newly recorded species in China; Pycnoporus sinoruber is a new species of the P. coccineus complex, differing from P. coccineus and P. sanguineus by shorter basidiospores and the more temperate distribution; Russula dulcicora is a new species in Russula sect. Heterophyllae subsect. Amoeninae, processing a unique combination of pinkish pileus and basidiospores sized 8.5–9.5 × 7–8.5 µm with subreticulate ornamentation.